Pelatihan Wasit Mini Soccer Di Kabupaten Gorontalo - Gani, Ardin; Fataha, Iwan (Jambura Arena Pengabdian, 2025)
The development of mini soccer in Gorontalo Province has shown a significant increase along with the growing number of tournaments at community, school, and regional levels. However, this growth has not been fully supported by the availability of professional and standardized refereeing human resources. Limited understanding of regulations, technical officiating skills, and decision-making abilities may negatively affect the quality of mini soccer competitions. This community service activity aimed to improve the competence and professionalism of mini soccer referees through a structured and practical training program. The training was conducted on November 16, 2025, in Pentadio District, Gorontalo Regency, and involved 20 participants from various regencies and cities in Gorontalo Province. The implementation employed a capacity-building approach that integrated lectures and interactive discussions, match-simulation-based field practice, as well as performance evaluation and reflection. The results indicated an improvement in participants’ understanding of mini soccer regulations, technical refereeing skills, decision-making abilities, and professional attitudes in officiating matches. The novelty of this program lies in the implementation of an integrated training model combining theoretical instruction, field practice, and reflective evaluation as the first structured mini soccer referee development program organized by the Gorontalo Provincial Board of the Indonesian Mini Soccer Committee (KSMI). This activity is expected to serve as a foundation for sustainable mini soccer referee development in the region.